2020
DOI: 10.1101/2020.09.18.304410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global timing mechanism regulates cell-type specific wiring programs

Abstract: Wiring a complex brain relies on cell-type and temporal-specific expression of genes encoding cell recognition molecules regulating circuit formation1–3. Though genetic programs driving cell-type specificity have been described4–6, how precise temporal control is achieved remains unknown. Here, we describe a global program for the temporal regulation of cell-type-specific wiring genes in the Drosophila visual system. We show that the Ecdysone Receptor induces a synchronous cascade of transcription factors in n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In addition, driver lines for specific types of PNs can be made using genes that show consistent expression pattern across different stages ( Figure 7—figure supplement 2 ) to label and genetically manipulate specific PN types. Together with several recent in depth scRNAseq studies of cells in the visual and olfactory system across multiple stages ( Jain et al, 2020 ; Kurmangaliyev et al, 2020 ; McLaughlin et al, 2021 ; Özel et al, 2021 ), these studies have established foundations of gene expression for Drosophila olfactory and visual systems and should catalyze new biological discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, driver lines for specific types of PNs can be made using genes that show consistent expression pattern across different stages ( Figure 7—figure supplement 2 ) to label and genetically manipulate specific PN types. Together with several recent in depth scRNAseq studies of cells in the visual and olfactory system across multiple stages ( Jain et al, 2020 ; Kurmangaliyev et al, 2020 ; McLaughlin et al, 2021 ; Özel et al, 2021 ), these studies have established foundations of gene expression for Drosophila olfactory and visual systems and should catalyze new biological discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in single-cell transcriptomics might provide a means to identify and decipher the combinatorial molecular codes that generate complex and cell-type-specific dendritic patterns ( Li et al, 2017 ; Kurmangaliyev et al, 2019 ; Davis et al, 2020 ). Stage-dependent gene expression, as revealed by developmental single-cell transcriptomics, has hinted at the importance of temporal regulation of extrinsic factors and receptors ( Jain et al, 2020 ; Kurmangaliyev et al, 2020 ; Özel et al, 2020 ). One study suggested that the temporal regulation of receptors and antagonistic regulation are required for robust control of dendritic sizes ( Luo et al, 2020 ), while other mechanisms of spatiotemporal regulation and combinatorial codes are being uncovered.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…Dendrite development requires specific intrinsic factors, such as transcriptional regulators, that facilitate growth of neurons and allow the cells to acquire subtype-specific morphologies ( Jan and Jan, 2010 ; Dong et al, 2015 ). Additionally, recent genetic and transcriptomic analyses have revealed that different types of neurons express distinct cell surface proteins that respond to external cues in order to guide and shape dendrites ( Li et al, 2017 ; Kurmangaliyev et al, 2019 ; Davis et al, 2020 ; Jain et al, 2020 ). This review focuses on the morphological aspects instructed by secreted and contact-mediated factors and the mechanisms by which extrinsic cues and key intrinsic regulators are spatiotemporally coordinated to shape dendritic patterning.…”
Section: Introduction: Dendritic Forms Follow Functionsmentioning
confidence: 99%